GIS-based estimation of biomass available and energy potential from corn residue in Bukidnon - Villar, Ricardo G. (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2016)
Biomass resources from forests and agriculture residues are underutilized and lost mostly in the provinces in Mindanao and other less developed areas in the country. This article focuses on the estimation of biomass available and energy potential of corn residue in Bukidnon. The study was carried out using survey questionnaires and government agriculture reports to investigate the potential biomass resources and the existing domestic and commercial uses of biomass in the province. Integration and analysis was done using ArcGIS platform and in mapping out geographic distribution and concentration of biomass resources. It is established that the annual biomass theoretical potential for Bukidnon is about 502,343.38 metric tonnes, which corresponds to an annual energy production potential of 2,252,016,879.08 MJ. Concentration of biomass theoretical potential is highest in District 2 and District 3 and consequently the energy potential of 144,220,522.03 kWH and 298,793.184.33 kWH, respectively. The outcomes of the present study indicate that for studies to develop site suitability analysis for power plant development including other leading agronomic crops may be considered.